The Geometric Construction of Traditional Settlement Space in the Ancient Village of Tenganan Dauh Tukad Karangasem Bali - I Komang Gede Santhyasa; Wahyudi Arimbawa; Komang Wirawan (Universitas Udayana, 2024)
The spatial arrangement of the Tenganan Dauh Tukad (TDT) settlement is perceived as the acculturation of Bali Aga (Old Bali) and Java Hindu Kingdom of Majapahit traditions. Accordingly, this study identifies the concepts, values, and philosophy behind residential space arrangement. Thus, this study enacted an interpretative approach. Data analysis was performed qualitatively in residential settings, i.e., culture, behavior, and spatial. This study demonstrated that the geometric construction of residential space in the TDT was formed in three manners. First, it blended the existing philosophy of harmony between the macrocosm and microcosm concepts. Second, the spatial arrangement of the TDT settlement adhered to the inward-oriented concept, with the village road as the central axis of village orientation. Third, cultural acculturation between the Bali Aga and Majapahit caused alterations in the settlement’s spatial orientation. This article contributes as a reference in creating traditional residential spaces that must consider socio-cultural aspects dynamically.